Chronic infectious lesions of the cervical spine in adults: monocentric cohort analysis and literature review - Denis G. Naumov; Sergey G. Tkach; Aleksandr Yu. Mushkin; Marina E. Makogonova (Хирургия позвоночника, 2021)
Objective. To analyze the results of surgical treatment of chronic infectious cervical spondylitis and literature data. Material and Methods. Design: retrospective monocentric cohort study for 2017–2020. The study included medical history and clini- cal and instrumental data of 25 patients who underwent 28 reconstructive surgeries on the suboccipital (n1 = 3) and subaxial (n2 = 25) spine. The average follow-up period was 1 year 2 months ± 4 months. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS), version 22.0. Results. The effect of the duration of the therapeutic pause (p = 0.043) and the T1 slope (T1S) (p = 0.022) on the intensity of verte- brogenic pain syndrome was established. When assessing the parameters of the sagittal balance a direct relationship between the age of patients and the value of cervical sagittal vertical axis (CSVA) (p = 0.035) was revealed, while CSVA (p = 0.514) and neck tilt angle (NTA) (p = 0.617) did not significantly affect the intensity of vertebral pain syndrome. The extent of vertebral destruction did not affect either the intensity of vertebral pain (p = 0.872) or the indices of the sagittal balance: CSVA (p = 0.116), T1S (p = 0.154), and NTA (p = 0.562). A significant predictor of postoperative complications is the level of comorbidity with an index of 7 or more (p = 0.027) ac- cording to the Charlson scale. Conclusion. The leading predictors of complications of surgical treatment of cervical infectious spondylitis are the Charlson comorbidity index (7 points or more) and the variant of anterior reconstruction (the use of a blocked extraspinal plate). The factors influencing the intensity of vertebrogenic pain syndrome in this pathology are the duration of the therapeutic pause and the magnitude of T1S compen- sation. Anterior reconstruction of the cervical spine in the presence of infectious spondylitis provides a correction of the sagittal balance parameters, with the possibility of long-term maintaining the achieved values.